Development of a wireless sensor network using ZigBee protocol for data monitoring and actuator activation (Research, Society and Development, 2020)
Wireless sensor networks have been widely used in recent years, both in industry and in homes, to automate environments. The study aims to develop a Wireless Sensor Network using the ZigBee protocol to monitor light, temperature and presence, with the addition of a load trigger lamp, in the monitored environment. As a result, the devices used to implement the network and the validation through tests performed were presented.